Characterization of biomaterials - Bandyopadhyay, Amit, 1967-; Bose, Susmita (Elsevier, 2013)
"The field of biomaterials is maturing as it expands beyond the first generation of general 'biomaterials' reference works. Demand for more specialized books is the necessary parallel. Today the field is inherently interdisciplinary, involving researchers from biology, materials science, tissue engineering, chemical engineering, mechanical engineering, chemistry, and physics. Such diversity creates an inherent problem - specifically in understanding the diverse universe of relevant characterization techniques that are needed to analyze and comprehend the characteristics of different biomaterials."--Resumé vydavatele